Oral Memoirs of Charles McCall - McCall, Charles (My University, 2016)
An oral history interview with Charles McCall, MD, former associate dean of the Tulsa Medical College, and later dean of the College of Medicine at the University of Oklahoma Health Sciences Center.
Keywords: University of Oklahoma. Tulsa Medical College -- History.; McCall, Charles -- Interviews.; McCall, Charles -- Career in medical education.; Medical education -- Oklahoma -- History.; Medical colleges -- Oklahoma -- History.; Physicians -- Interviews.